Public Display Of Affection, Is It Reasonable To Do It?: Study At Tapal Kuda Beach, Ambon City - Joia Nussy; Hermien. L. Soselisa; Simona Ch. H Litaay (LPPM Universitas PGRI Sumatera Barat, 2024)
This research focuses on public perceptions at the Tapal Kuda tourist attraction, Nusaniwe Village, Nusaniwe District, Ambon City regarding Public Display of Affection (PDA) behavior. The aim of this research is to determine public perceptions of PDA behavior and the motives of PDA perpetrators. This research is qualitative research, to find data in the field it was carried out using observation, interviews and documentation methods. The results of this research show that PDA is a behavior showing affection in public, and this behavior causes different reactions and perceptions in society, some of whom agree and do not object to this behavior but many people also disagree because PDA is considered as behavior that violates social values and norms in the social order.